Repair of an adult aorto‐pulmonary artery fistula associated with a ruptured aortic arch aneurysm using a frozen elephant trunk technique. Issue 10 (21st September 2018) - Nakamura, Ryo; Honda, Kentaro; Yuzaki, Mitsuru; Nakai, Takeo; Kunimoto, Hideki; Nishimura, Yoshiharu
Abstract: We describe the repair of an acute aorto‐pulmonary artery fistula in a 82‐year‐old patient with a ruptured aortic arch aneurysm using a frozen elephant trunk technique.